Maturasi dan erupsi gigi permanen pada anak periode gigi pergantian (The maturition and eruption of permanent teeth in mixed dentition children) - Sri Kuswandari (Dental Journal (Majalah Kedokteran Gigi), 2014)
Background: Tooth eruption might used as predictor of child age when the chronologic age is unknown. Beside the dental maturity, tooth eruption is also influenced by some factors, such as caries and tooth extraction. Purpose: The aim of this research was to examine the relationship of maturity and eruption of permanent teeth with chronologic age in mixed dentition period children. Methods: The subjects were patients of Prof. Soedomo Dental Hospital Pediatric Dental Clinic, consist of 38 boys and 39 girls in the aged of 6-12 years. The tooth eruption data was taken by counting the permanent teeth in intra oral examination. The dental maturity was assessed by Dermijian method from dental panoramic radiology. The data were statistical analyzed by regresion-correlation and t-test program of SPSS 16.0 for Windows. Results: Maturation of permanent teeth in each of age group was more advanced in girls than boys. However, only groups of 7, 8 and 11 years were showed significant different (p<0.05), while for tooth eruption there was no significant difference (p>0.05). The coefficient correlation between tooth eruption, chronologic age and dental maturation scores were relative high, between 0.75–0.86 (p<0.01). The contribution of chronologic age and dental maturation to predict tooth eruption (R2) were 58–73.6%. The Dermijian method predicted age 0.83 years higher. Conclusion: There were close relationship between chronologic age, Dermijian method dental maturity, and eruption of permanen tooth, and could be used as predictor for eruption of permanent teeth in the mixed dentition period children. The Dermijian method predicted 0.83 years older than the chronologic age.Latar belakang: Erupsi gigi sering digunakan untuk memperkirakan umur anak. Selain maturasi gigi, erupsi gigi juga dipengaruhi oleh faktor, seperti karies dan pencabutan gigi. Tujuan: Penelitian ini bertujuan untuk meneliti hubungan antara maturasi dan erupsi gigi permanen dengan umur pada anak periode gigi bercampur. Metode: Subjek terdiri atas 38 anak laki-laki dan 39 anak perempuan berumur 5,98–11,90 tahun pasien klinik Ilmu Kedokteran Gigi Anak Rumah Sakit Gigi dan Mulut Prof. Soedomo, Fakultas Kedokteran Gigi Universitas Gadjah Mada. Penghitungan jumlah gigi permanen yang telah erupsi dilakukan dengan pemeriksaan klinis. Penentuan maturitas gigi metode Dermijian dilakukan dengan rontgen panoramik. Analisis statistik dengan regresi korelasi dan uji t program SPSS 16,0 for Windows. Hasil: Maturasi gigi permanen pada anak perempuan tiap kelompok umur lebih tinggi dibandingkan pada anak laki-laki, tetapi hanya pada kelompok umur 7, 8 dan 11 menunjukkan perbedaan bermakna (p<0,05). Tidak ada perbedaan bermakna (p>0,05) erupsi gigi antara laki-laki dan perempuan. Koefisisen korelasi antar erupsi gigi, umur kronologis, skor maturasi gigi cukup tinggi, yaitu 0,75–0,86 (p<0,01). Kontribusi umur kronologis dan maturasi gigi dalam memprediksi erupsi gigi (R2) berkisar > 58–73,6%. Metode Dermijian memprediksi umur 0,83 tahun lebih tinggi. Simpulan: Antara umur kronologis, maturasi gigi metode Dermijian dan erupsi gigi berhubungan erat, dan merupakan prediktor yang baik bagi erupsi gigi pada anak periode gigi bercampur. Metode Dermijian memprediksi 0,83 tahun lebih tinggi dibandingkan umur kronologis.